Feline Hemotropic Mycoplasma Species of Apparently Healthy Domestic Cats in Konya Province of Türkiye - Ceylan Ceylan; Muhammed Hudai Culha; Gonca Sonmez; Muhammed Ahmed Selcuk; Merve Ider; Ayşe Evci; Sule Yılmaz; Ferda Sevinc; Onur Ceylan (Veterinary Sciences)
Feline hemotropic mycoplasmosis is an emerging infectious disease in domestic cats caused by a group of hemotropic Mycoplasma species, including three main species: Mycoplasma hemofelis (Mhf), Candidatus Mycoplasma hemominutum (CMhm), and Candidatus Mycoplasma turicensis (CMt). The primary objective of this investigation was to ascertain the molecular prevalence and characterization of hemotropic mycoplasmas in domestic cats from twenty-three districts of Konya province in Türkiye. For this purpose, 384 apparently healthy cats belonging to different breeds were enrolled in this study. The molecular prevalence of Mycoplasma spp. in cats was 9.4%, and the identified species included Mhf, Mycoplasma hemocanis (Mhc), CMt, and CMhm. The molecular prevalence was not significantly associated with district, breed, or gender (p > 0.05) but was significantly associated with age and ownership status (p < 0.05). The study found that all cats with Mycoplasma spp. were older than one year and that the infection had a higher prevalence in stray cats than in owned cats (p < 0.05). Although there are studies conducted in different provinces, data on the molecular and phylogenetic characterization of the species causing feline hemotropic mycoplasmosis are scarce in Türkiye. This study, which provides updated data concerning the molecular characterization and phylogeny of hemotropic Mycoplasma species of cats in Türkiye, revealed the Mycoplasma spp. molecular prevalence in Konya province for the first time and provided remarkable findings that will fill the scientific gap in the country. The molecular characterization of these hemotropic mycoplasmas is crucial for understanding their epidemiology and developing effective diagnostic and treatment strategies for feline hemotropic mycoplasmosis. It is anticipated that the data from the study will raise awareness among pet owners, veterinarians, and healthcare professionals of feline hemotropic Mycoplasma agents with zoonotic potential.